Dimethyl fumarate impairs differentiated B cells and fosters central nervous system integrity in treatment of multiple sclerosis - Traub, Jan (Brain Pathol, 2019)
In multiple sclerosis (MS), the effect of dimethyl fumarate (DMF) treatment is primarily attributed to its capacity to dampen pathogenic T cells. Here, we tested whether DMF also modulates B cells, which are newly recognized key players in MS, and to which extent DMF restricts ongoing loss of oligodendrocytes and axons in the central nervous system (CNS). Therefore, blood samples and brain tissue from DMF‐treated MS patients were analyzed by flow cytometry or histopathological examination, respectively. Complementary mechanistic studies were conducted in inflammatory as well as non‐inflammatory CNS demyelinating mouse models. In this study, DMF reduced the frequency of antigen‐experienced and memory B cells and rendered remaining B cells less prone to activation and production of pro‐inflammatory cytokines. Dissecting the functional consequences of these alterations, we found that DMF ameliorated a B cell‐accentuated experimental autoimmune encephalomyelitis model by diminishing the capacity of B cells to act as antigen‐presenting cells for T cells. In a non‐inflammatory model of toxic demyelination, DMF limited oligodendrocyte apoptosis, promoted maturation of oligodendrocyte precursors and reduced axonal damage. In a CNS biopsy of a DMF‐treated MS patient, we equivalently observed higher numbers of mature oligodendrocytes as well as a reduced extent of axonal damage when compared to a cohort of treatment‐naïve patients. In conclusion, we showed that besides suppressing T cells, DMF dampens pathogenic B cell functions, which probably contributes to its clinical effectiveness in relapsing MS. DMF treatment may furthermore limit chronically ongoing CNS tissue damage, which may reduce long‐term disability in MS apart from its relapse‐reducing capacity.